2014
DOI: 10.1371/journal.pone.0099745
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Forward Maskers Affect Auditory Intensity Discrimination? Evidence from "Molecular Psychophysics"

Abstract: Nonsimultaneous maskers can strongly impair performance in an auditory intensity discrimination task. Using methods of molecular psychophysics, we quantified the extent to which (1) a masker-induced impairment of the representation of target intensity (i.e., increase in internal noise) and (2) a systematic influence of the masker intensities on the decision variable contribute to these effects. In a two-interval intensity discrimination procedure, targets were presented in quiet, and combined with forward mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
(137 reference statements)
1
12
1
Order By: Relevance
“…Whereas the results of the present study are consistent with peripheral mechanisms leading to decreased WFs at the mid-level hump, previous studies have shown that WFs measured in the context of the Zeng Bump may be altered via more central mechanisms. Specifically, the Zeng Bump can be decreased by altering the perceived spatial separation of the masker and pedestal by manipulating masker interaural time difference while leaving the peripheral representations intact (Oberfeld et al, 2012(Oberfeld et al, , 2014 or by presenting a noise burst after the pedestal (Plack et al, 1995). In the present study, neither backward NN nor backward NBN led to decreased WFs at the midlevel hump.…”
Section: Comparison To Previous Intensity Discrimination Workcontrasting
confidence: 65%
“…Whereas the results of the present study are consistent with peripheral mechanisms leading to decreased WFs at the mid-level hump, previous studies have shown that WFs measured in the context of the Zeng Bump may be altered via more central mechanisms. Specifically, the Zeng Bump can be decreased by altering the perceived spatial separation of the masker and pedestal by manipulating masker interaural time difference while leaving the peripheral representations intact (Oberfeld et al, 2012(Oberfeld et al, , 2014 or by presenting a noise burst after the pedestal (Plack et al, 1995). In the present study, neither backward NN nor backward NBN led to decreased WFs at the midlevel hump.…”
Section: Comparison To Previous Intensity Discrimination Workcontrasting
confidence: 65%
“…On average, the segments in the second interval received significantly higher weights than the segments in the first interval, d z = 1.38. Ah igher reliance on the second observation interval in 2I discrimination tasks wasr eported by several previous studies [17,54,55,56]. The segment × interval and the segment × levelprofile × interval interactions were also significant.…”
Section: Temporal Weightssupporting
confidence: 62%
“…Although grouping does not explain why target perception deteriorates in crowding, our results show that perceptual organization plays a crucial role in predicting crowding strength. Perceptual organization has been shown to play a role also in many other visual processes, like surround suppression (Saarela & Herzog, 2009a), metacontrast masking (Duangudom, Francis, & Herzog, 2007), visual short-term memory (Kahneman, 1973), and audition (Bregman, 1981;Oberfeld, Stahn, & Kuta, 2014).…”
Section: Discussionmentioning
confidence: 99%